2016
DOI: 10.1515/pjvs-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in reticulorumen content temperature and pH according to time of day and yearly seasons

Abstract: The monitoring of rumen content temperature can be useful for the evaluation of cow health condition and heat. The aim of this research was to evaluate the influence of the circadian rhythm (time of day) and season on reticulorumen acidity (pH) and temperatures (RT) in lactating dairy cows. The research was performed on ten 2 nd -lactation, clinically healthy Lithuanian Black and White fresh dairy cows (up to 1 day after calving). The cows were milked twice daily at 05:00 and 17:00. The cows were kept in a loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The relationship between the external drivers of feed intake and the intrinsic rhythm of rumination may affect the digestion of feeds and rumen buffering. Most experiments show that rumen pH reaches a nadir approximately 7 to 9 h after feed delivery in cows fed a TMR once or twice per day, but the pattern varies among experiments (Dado and Allen, 1993; Nikkhah et al, 2011; Antanaitis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the external drivers of feed intake and the intrinsic rhythm of rumination may affect the digestion of feeds and rumen buffering. Most experiments show that rumen pH reaches a nadir approximately 7 to 9 h after feed delivery in cows fed a TMR once or twice per day, but the pattern varies among experiments (Dado and Allen, 1993; Nikkhah et al, 2011; Antanaitis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According Renaudeau et al [5] heat-stressed dairy cows reduced the feed intake to avoid excessive metabolic heat production, while maintenance costs increased [49]. However, recently, it was demonstrated that reduced intake accounted for only 35% of the decline in milk yield under heat stress conditions, and it was suggested that a shift in postabsorptive metabolism and nutrient partitioning might account for the remaining reduction in milk yield [50]. Mean air temperature had the greatest influence on milk yield for Holstein cows fed high or low concentrate diets under hot conditions [51].…”
Section: Heat Stress and Rt Bw And CCmentioning
confidence: 99%
“…Cellulolytic bacteria digest fiber effectively at this pH level, which is inhibited at pH values lower than 6.0 [ 10 ]. As a result, a decrease in ruminal pH increases acidity, which increases abomasum temperature [ 11 ]. The reticuloruminal temperature monitoring clearly reflects the cows’ feed- and water-consumption habits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%